A Review of Gadamer's Hermeneutics of Syuhudi Ismail's Concept of Hadith Contextualization - Raadliyatush Shalihah; Hamzah, Muhammad Habibi (Ulumuna: Jurnal Studi Keilsman, 2025)
Syuhudi Ismail is an Indonesian hadith scholar who has a new concept in understanding hadith, namely by contextualizing hadith and characterizing hadith with temporal, local and universal. In this study, the concept of contextualization of hadith of Syuhudi Ismail is reviewed hermeneutically from Gadamer's hermeneutic theory. The purpose of this research is to find out Syuhudi Ismail's concept in contextualizing hadith and to review it with Gadamer's hermeneutic theory. This study uses library research method by referring to books by Syuhudi Ismail especially Syuhudi Ismail's book entitled Textual and Contextual Hadith and scientific articles that discuss the work of Syuhudi Ismail in contextualizing hadith as well as scientific articles about Gadamer's hermeneutics and examples of its application. In Gadamer's hermeneutics there are aspects that need to be considered and these aspects are reviewed from the contextual interpretation of Syuhudi Ismail's hadith so that both involve socio-historical, contextual aspects and fuse the two so as to give birth to a relatve new meaning. As in the interpretation of the Hadith about the threat to painters, Syuhudi Ismail interprets the Hadith by presenting the socio-historical aspect which is used as the 'illat of the Hadith which if the 'illat of this Hadith is lost, it will affect the meaning of the Hadith.